Seriousness and women’s roller derby : gender, organization and ambivalence - Breeze, Maddie (Palgrave Macmillan, 2020)
This book explores seriousness in practice in the unique sports context of contemporary women's flat track roller derby. The author presents a stimulating argument for a sociology of seriousness as a productive contribution to understandings of gender, organization and the mid-ranges of agency between dichotomies of voluntarism and determinism